Cap-and-Trade or Carbon Taxes? The Feasibility of Enforcement and the Effects of Non-Compliance - Jon Hovi; Bjart Holtsmark (Statistics Norway, Research Department, 2005)
One of the proposed alternatives to Kyoto's cap-and-trade approach is a regime based on an internationally harmonized carbon tax. In this paper, we consider and compare the enforcement problems associated with a tax regime and a cap-and-trade regime, respectively. The paper tries to convey two main points. First, both types of regime require an effective enforcement mechanism. However, such a mechanism is unlikely to be adopted as part of a regime with full participation, because the political process leading up to its adoption tends to water down the enforcement mechanism to a point where it no longer has much bite. And even if this is somehow avoided, countries expecting compliance to be difficult or costly will almost certainly decline to sign - not to mention ratify - the resulting agreement. Second, the implications of non-compliance in a tax regime differ in important ways from the corresponding implications in a cap-and-trade regime. In a cap-and-trade regime emissions trading can make inaction legitimate for buyers of emission permits. In particular, overselling of permits by one (or a few) permit exporting countries might completely undermine the regime's environmental effect. In a tax regime, by contrast, one country's non-compliance can not make inaction by other countries legitimate. It follows that an agreement based on a harmonized carbon tax will always have some effect, provided that at least one country complies.
Keywords: Q30; Q41; 330; Climate agreements; compliance; enforcement; emissions trading; carbon taxes.